2011
DOI: 10.1002/bies.201100057
|View full text |Cite
|
Sign up to set email alerts
|

How ubiquitination regulates the TGF‐β signalling pathway: New insights and new players

Abstract: Subtitle:TGF-β regulation by NEDD4 E3s are discussed, while emphasising the potential role of isoform-derivatives of E1-E3 proteins in ubiquitination.Key Words: TGF beta, Smad, Ubiquitination, Uniquitinome, EMT, cancer Abstract Ubiquitination of protein species in regulating signal transduction pathways is universally accepted as fundamental during normal development and has been implicated in the progression of many human diseases, such as cancer. One particular pathway that has received much attention in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 111 publications
0
19
0
Order By: Relevance
“…This modification is more versatile than other post-translational modifications because several ubiquitin molecules can be added to the first, creating chains of ubiquitin on the target proteins that modify the signal [36]. The ubiquitin proteasome system regulates all processes that are involved in carcinogenesis, among them invasion and metastasis, EMT, the process that endows neoplastic cells with invasive and metastatic potential, is intimately interwoven with other neoplastic processes, being served by several common pathways, several of which are regulated by the ubiquitin proteasome system [37]. USP28 is a key regulator of the DNA damage checkpoint, high expression levels of USP28 are found in colon and breast carcinomas, and stabilization of MYC by USP28 is essential for tumour-cell proliferation [38].…”
Section: Discussionmentioning
confidence: 99%
“…This modification is more versatile than other post-translational modifications because several ubiquitin molecules can be added to the first, creating chains of ubiquitin on the target proteins that modify the signal [36]. The ubiquitin proteasome system regulates all processes that are involved in carcinogenesis, among them invasion and metastasis, EMT, the process that endows neoplastic cells with invasive and metastatic potential, is intimately interwoven with other neoplastic processes, being served by several common pathways, several of which are regulated by the ubiquitin proteasome system [37]. USP28 is a key regulator of the DNA damage checkpoint, high expression levels of USP28 are found in colon and breast carcinomas, and stabilization of MYC by USP28 is essential for tumour-cell proliferation [38].…”
Section: Discussionmentioning
confidence: 99%
“…FHOD1 is an actin-nucleating formin that is primarily involved in the cytoskeletal rearrangement and is upregulated during EMT transition (Gardberg et al, 2013) while PPM1F kinase is involved in MAP kinase regulation of focal adhesion (Zhang S. et al, 2013). In lung cancer, miR-200c inhibits cancer cell invasion through the ubiquitin specific peptidase 25 ( USP25 ) protein (Li J. et al, 2014), which is a peptidase primarily associated with protein ubiquitination and may intervene with TGFβ signaling and EMT (Soond and Chantry, 2011). A recent study on breast cancer to identify the functional targets of miR-200c revealed that among 12 validated targets, CRTAP was shown to be strongly implicated in cell invasion (Perdigao-Henriques et al, 2016).…”
Section: Mir-200c-mediated Metastasismentioning
confidence: 99%
“…Although several chain types exist, not all have been attributed a function. Of the commonly studied, K48 chains are known to signal degradation, whereas K63 chains play a role in signalling as well as protein trafficking and endocytosis [9,10]. …”
Section: Introductionmentioning
confidence: 99%